Navigating Hyperinflation: The Role of Accounting Information in Enhancing Value Relevance in Emerging Economies - Newman WADESANGO; Panashe Hillary NYAKUYA (CECCAR Business Review)

(untitled)
This research explores the unique challenges and financial reporting practices in hyperinflationary settings, focusing on Lester Quality Products as a case study. The study defines hyperinflation, evaluates the role of International Accounting Standard (IAS) 29 Financial Reporting in Hyperinflationary Economies in enhancing the quality of financial reporting, and highlights the need for manufacturing firms to adapt their financial statements. Using a mixed-methods approach, data was collected through questionnaires and interviews with key stakeholders. The findings reveal that hyperinflation distorts valuations of money and assets, complicating the assessment of LQP’s actual performance and stability. As a remedy, financial statements require restatement to reflect the rapid erosion of purchasing power, employing techniques such as the Current Purchasing Power method and General Price Level Accounting. This study underscores the urgency of investing in accounting training programs to alleviate the shortage of qualified professionals, while emphasizing the need for robust regulatory oversight to ensure financial statement integrity. By addressing these critical issues, the research provides valuable insights for policymakers, practitioners, and academics worldwide, enhancing the relevance and precision of financial reporting in hyperinflationary economies.